The Existence of Islamic Boarding School Curriculum After the Enactment of Law Number 18 of 2019 Concerning Islamic Boarding Schools (A Comparative Multi-Case Study of Salafiyah and Modern Islamic Boarding Schools) - Masyhari Yanto; Yusfar Ramadhan (Community: Jurnal Hasil Penelitian dan Pengabdian Masyarakat, 2026)
Law Number 18 of 2019 concerning Islamic Boarding Schools (Pesantren) provides formal recognition and pressure for standardization of Islamic boarding school curricula. This study aims to analyze the existence and transformation of Islamic boarding school curricula post-law, identify challenges and opportunities for implementation, and explore stakeholder responses. This study uses a qualitative approach with a comparative multi-case study design. The research locations are the Al-Hamidy Islamic Boarding School in Banyuanyar (Salafiyah) and the Ma'had TMI Al-Amien Prenduan (Modern) in Sumenep Regency, Madura. Data were collected through in-depth interviews, participant observation, and document study. Data analysis used the Miles, Huberman, and Saldana model with two levels: within-case and cross-case analysis. Data validity was maintained through triangulation of sources and methods. The findings reveal distinct patterns of adaptation. The Salafiyah Islamic boarding school (Al-Hamidy) demonstrates a fundamental transformation from a standardized oral to a written curriculum, but maintains the essence of the yellow books by making the national curriculum an extracurricular activity (selective resistance). In contrast, modern Islamic boarding schools (TMI), which have had a mature curriculum since 1971, demonstrate strong continuity; the law actually serves as a legal umbrella that strengthens the existing system (creative adaptation). Stakeholder responses are diverse: caregivers are adaptive and negotiative, educators (teachers) feel new administrative burdens but are motivated by devotion to the kiai, and students respond positively with the hope of mastering religious and general knowledge. The existence of the Islamic boarding school curriculum after Law No. 18/2019 has not disappeared but has transformed, marked by a dialectic between traditional autonomy and demands for standardization. The implication is that the government needs to adopt a differentiated policy approach and technical assistance to accommodate the diversity of Islamic boarding school models. Institutional theory is enriched by showing that coercive pressure (coercive isomorphism) does not always eliminate the uniqueness of the institution if balanced with a strong negotiation strategy.